Effects of transcranial combined with peripheral repetitive magnetic stimulation on limb spasticity and resting-state brain activity in stroke patients - Qin, Yin; Liu, Xiaoying; Zhang, Yinxin; Wu, Jiwei; Wang, Xiaoyang (Frontiers in Human Neuroscience, 2023)
Background and Objective: Transcranial magnetic stimulation and peripheral repetitive magnetic stimulation (rPMS), as non-invasive neuromodulation techniques, can promote functional recovery in patients with post-stroke spasticity (PSS), but the effects of transcranial magnetic stimulation combined with peripheral magnetic stimulation on PSS remain largely unknown. Therefore, we examined the effects of low-frequency repetitive transcranial magnetic stimulation (LF-rTMS) combined with rPMS on PSS patients and its potential neural correlates to behavioral improvements. Methods: Forty-nine PSS patients were divided randomly into three groups: a combined group (n=20), a LF-rTMS group (n=15) and a control group (n=14). The combined group received LF-rTMS and rPMS treatment, the rTMS group received LF-rTMS treatment, and the control group received only routine rehabilitation. All patients underwent Ashworth Spasm Scale (MAS), upper extremity Fugl-Meyer (FMA-UE), and modified Barthel Index (MBI) assessments before and after intervention. In addition, resting-state functional magnetic resonance imaging data were collected pre- and post-treatment to observe changes in the amplitude of low-frequency fluctuation (ALFF). Results: The MAS score was decreased, FMA-UE score and MBI scores were increased in the three groups after therapy than before therapy (all P<0.05). In particular, the combined group showed significant effect on improved motor function and relieved spasticity in PSS (P<0.01). Moreover, the combined treatment increased ALFF values mainly in the right supplementary motor area, right middle frontal gyrus, and right cerebellum, while reduced ALFF values mainly in the right postcentral gyrus compared with pretreatment. Compared with the LF-rTMS and control groups, the combined treatment increased ALFF values in the right cerebellum and reduced ALFF values mainly in the frontoparietal cortex. Improvements in the MAS score were positively correlated with the change in ALFF values in the right cerebellum (r = 0.698, P = 0.001) and the right supplementary motor area (r = 0.700, P = 0.001) after combined treatment. Conclusions: Transcranial combined with peripheral repetitive magnetic stimulation could improve spastic state and motor function in PSS patients, and this effect may be associated with altered cerebellar and frontoparietal cortical activity.